Genome-wide identification of the heat shock transcription factor gene family in two kiwifruit species - Tu, Jing; Abid, Muhammad; Luo, Juan; Zhang, Yi; Yang, Endian; Cai, Xinxia; Gao, Puxin; Huang, Hongwen; Wang, Zupeng (Frontiers in Plant Science, 2023)
High temperatures have a significant impact on plants growth and metabolism. In recent years, the fruit industry has faced a serious threat due to high-temperature stress on fruit plants caused by global warming. In the present study, we explored the molecular regulatory mechanisms that contribute to high-temperature tolerance in kiwifruit. A total of 36 Hsf genes were identified in the A. chinensis (Ac) genome, while 41 Hsf genes were found in the A. eriantha (Ae) genome. Phylogenetic analysis revealed the clustering of kiwifruit Hsfs into three distinct groups (group A, B, and C). Synteny analysis indicated that the expansion of the Hsf gene family in the Ac and Ae genomes was primarily driven by whole genome duplication (WGD). Analysis of the gene expression profiles revealed a close relationship between the expression levels of Hsf genes and various plant tissues and stress treatments throughout fruit ripening. Subcellular localization analysis demonstrated that GFP-AcHsfA2a/AcHsfA7b and AcHsfA2a/AcHsfA7b -GFP were localized in the nucleus, while GFP-AcHsfA2a was also observed in the cytoplasm of Arabidopsis protoplasts. The results of real-time quantitative polymerase chain reaction (RT-qPCR) and dual-luciferase reporter assay revealed that the majority of Hsf genes, especially AcHsfA2a, were expressed under high-temperature conditions. In conclusion, our findings establish a theoretical foundation for analyzing the potential role of Hsfs in high-temperature stress tolerance in kiwifruit. This study also offers valuable information to aid plant breeders in the development of heat-stress-resistant plant materials.